汉语网络流行语对学习汉语兴趣的影响分析 - Devika Berty; Lily Thamrin; Yoanna Afrimonika (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractChinese Internet buzzwords are some words that are popular on the Internet. They gradually enter people's lives and change people's traditional expressions. Chinese Internet buzzwords have the characteristics of modernity, simplicity, high frequency, and intuitiveness. The emergence of Chinese Internet buzzwords is a new thing for learners of Chinese as a foreign language. It has brought many influences in the process of students learning Chinese. In order to understand the cognition of Chinese language online buzzwords by students majoring in Chinese language education at Tanjung Pura University, and to understand the influence of students majoring in Chinese language education at Tanjung Pura University on their interest in learning Chinese, the author consulted relevant information for the future Research as a good foundation. The author uses the test research method, the questionnaire research method and the interview research method to study the students majoring in Chinese language education at Tanjung Pura University. The test research method is about the students' cognition of Chinese Internet buzzwords, while the questionnaire method and interview research method are about the influence of Chinese Internet buzzwords on the interest in learning Chinese. From the survey results, the author found that students fail to recognize Chinese internet buzzwords because the correct rate reached 48.19%. It is easier for students to understand and use intuitive Internet buzzwords, while it is more difficult for students to understand modern Internet buzzwords. In the process of students learning Chinese, Chinese Internet buzzwords have brought a very good influence. Students are very willing to learn Chinese Internet popular words, increase students' interest in learning Chinese, improve their oral Chinese ability, and increase their vocabulary. At the same time, for students, being able to understand the current social dynamics and culture in China can help students increase their circle of friends and generate topics that are unified with the Chinese.KeyWord: Chinese internet buzzwords, Affect, Learning interest